Color‐Selective 2.5D Holograms on Large‐Area Flexible Substrates for Sensing and Multilevel Security. Issue 10 (5th July 2016) - Yetisen, Ali K.; Butt, Haider; Mikulchyk, Tatsiana; Ahmed, Rajib; Montelongo, Yunuen; Humar, Matjaž; Jiang, Nan; Martin, Suzanne; Naydenova, Izabela; Yun, Seok Hyun
Abstract : 2.5D photonic nanostructures with narrow‐band diffraction characteristics have a vast range of potential applications in information storage, tunable lasers, optical filters, and biosensors. However, fabrication of 2.5D photonic devices over large areas remains expertise‐dependent, inaccurate, and high‐cost, limiting their widespread use in practical applications and consumer products. Here, large area printing of quasi 2.5D holograms is demonstrated in the visible spectrum. These holographic surface‐relief gratings are hexagonally packed lateral microscale honeycomb pyramids consisting of vertical nanoscale steps. The consecutive steps act as Bragg gratings producing constructive interference of selective visible wavelengths. The 2.5D nanostepped pyramids exhibit coloration due to the narrow‐band Bragg diffraction that is tuned in the visible spectrum and a wide angular range. Roll‐to‐roll processing allows for rapid nanoimprinting the 2.5D nanostepped pyramid arrays over large areas of acrylate polymer film on poly(ethylene terephthalate) substrate. The utilities of the 2.5D holograms are demonstrated by creating colorimetric refractive index and relative humidity sensors, quick response codes, fingerprints, signatures, and encrypted labels. It is envisioned that 2.5D holograms can be integrated with desktop dot‐matrix printers for application in sensing, data storage, and security. Abstract : 2.5 dimensional (2.5D) nanostepped holograms are produced over large flexible substrates using nanoimprinting. The 2.5D structures exhibit coloration due to Bragg diffraction that is tuned in the visible spectrum at a wide angular range. Applications are demonstrated in sensing, security labels, QR codes, and signatures.